2022
DOI: 10.1155/2022/2569810
|View full text |Cite
|
Sign up to set email alerts
|

Power Swing and Fault Detection in the Presence of Wind Farms Using Generator Speed Zero-Crossing Moment

Abstract: Nowadays, due to the entry of wind power plants into the power systems, which causes changes in the network parameters, power swing detection has become more important. Changes in the wind speed and noncontinuity of the wind power plants lead to changes in the power swing characteristic. Therefore, the impedance seen by the distance relay is changed, and so the maloperation of the relay during the stable power swing may occur. This paper proposes a new method to detect power fluctuations based on the synchrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For the considered turbines (600 kW), the values are R = 31.2 m,ρ= 1.225 kg/m 3 and C P calculation is taken from (Damchi and Eivazi, 2022).…”
Section: Turbine Rotor and Associated Disturbances Modelmentioning
confidence: 99%
“…For the considered turbines (600 kW), the values are R = 31.2 m,ρ= 1.225 kg/m 3 and C P calculation is taken from (Damchi and Eivazi, 2022).…”
Section: Turbine Rotor and Associated Disturbances Modelmentioning
confidence: 99%
“…Therefore, the successful integration of wind power at a global level relies heavily on accurate wind power prediction. It is demonstrated that challenges such as insufficient regulation and reserve power, often linked to the variability and limited predictability of wind power, can only be comprehensively evaluated when considering the characteristics of the conventional generation system with which wind power is integrated [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of this model was subsequently evaluated to assess its performance. In [5], CNN and a physical model were integrated to enhance the accuracy of short-term wind power forecasting, significantly reducing forecasting errors. In [15], LSTM models have been utilised in short-term wind speed and power forecasting.…”
Section: Introductionmentioning
confidence: 99%